Post-Euromaidan Ukraine : Domestic Power Struggles and War of National Survival in 2014-2022. - Harasymiw, Bohdan; Umland, Andreas (Berlin : Ibidem Verlag, 2023)
Ukraine is a misfit among post-communist states, being neither a respectable, stable democracy nor an autocracy. Nor does it sit well as a patronal political system, like other post-Soviet regimes, since the Euromaidan Revolution. This study examines the presidencies of Petro Poroshenko and Volodymyr Zelenskyy focusing on their common tendency to subordinate the legal system and use it as a political instrument. It finds that this pattern of power struggle concentrated in the president's office was, contrary to the theory of patronal politics, more dominant than clientelism. The second theme of this book is each president's handling of relations--largely meaning the war--with Russia, in the wake of the annexation of Crimea in 2014 and culminating in the invasion of 2022, as the key challenge to the nation's survival. One way or another, unable to reform itself or to withstand the Russian assault, post-Euromaidan Ukraine will have come to an end.
Ukraine and the War -- Politics Never Sleeps -- Conclusion -- 6. Conclusion -- On Patronal Politics in Post-2014 Ukraine -- Poroshenko's Presidency -- Zelenskyy's Presidency -- On Putin's War -- War's Impact on Ukraine -- Ukraine and the World -- Bibliography -- Books and book chapters -- Websites -- Newspapers, news sites, and newsmagazines -- Miscellaneous -- Conference paper -- Index
Description based upon print version of record.
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Russo-Ukrainian War, 2014-; Russia (Federation) -- Foreign relations -- Ukraine; Ukraine -- Foreign relations -- Russia (Federation); Ukraine -- Foreign relations -- 1991-2014.; Russian Invasion of Ukraine, 2022.; Guerre russo-ukrainienne, 2014-; Ukraine -- Relations extérieures -- Russie; Ukraine -- Relations extérieures -- 1991-2014.; Diplomatic relations; Russia (Federation); Ukraine; Since 1991